Application of nanotechnology for the development of microbicides. (29th December 2016) - Brako, Francis; Mahalingam, Suntharavathanan; Rami-Abraham, Bahijja; Craig, Duncan Q M; Edirisinghe, Mohan
Abstract: The vaginal route is increasingly being considered for both local and systemic delivery of drugs, especially those unsuitable for oral administration. One of the opportunities offered by this route but yet to be fully utilised is the administration of microbicides. Microbicides have an unprecedented potential for mitigating the global burden from HIV infection as heterosexual contact accounts for most of the new infections occurring in sub-Saharan Africa, the region with the highest prevalent rates. Decades of efforts and massive investment of resources into developing an ideal microbicide have resulted in disappointing outcomes, as attested by several clinical trials assessing the suitability of those formulated so far. The highly complex and multi-level biochemical interactions that must occur among the virus, host cells and the drug for transmission to be halted means that a less sophisticated approach to formulating a microbicide e.g. conventional gels, etc may have to give way for a different formulation approach. Nanotechnology has been identified to offer prospects for fabricating structures with high capability of disrupting HIV transmission. In this review, predominant challenges seen in microbicide development have been highlighted and possible ways of surmounting them suggested. Furthermore, formulations utilising some of these highly promising nanostructures such as liposomes, nanofibres and nanoparticles have been discussed. A perspective on how a tripartite collaboration among governments and their agencies, the pharmaceutical industry and academic scientists to facilitate the development of an ideal microbicide in a timely manner has also been briefly deliberated.